2017
DOI: 10.1016/j.neurobiolaging.2017.01.009
|View full text |Cite
|
Sign up to set email alerts
|

The Down syndrome brain in the presence and absence of fibrillar β-amyloidosis

Abstract: People with Down syndrome (DS) have a neurodevelopmentally distinct brain and invariably developed amyloid neuropathology by age 50. This cross-sectional study aimed to provide a detailed account of DS brain morphology and the changes occuring with amyloid neuropathology. Forty-six adults with DS underwent structural and amyloid imaging—the latter using Pittsburgh compound B (PIB) to stratify the cohort into PIB-positive (n = 19) and PIB-negative (n = 27). Age-matched controls (n = 30) underwent structural ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 61 publications
6
51
1
3
Order By: Relevance
“…Similar regions underwent changes in PiB SUVR, FDG SUVR, and GM volume as reported in Sabbagh et al [32] and those changes are driven by older, PiB(+) or demented participants. A number of other studies have investigated these three biomarkers in the DS population to varying extents [26, 31, 49, 5963]. As an extension of the current literature, we incorporated information from all three biomarkers into a single multi-modal voxel-wise model, and verified the regional specificity of AD-related neurodegeneration in DS.…”
Section: Discussionmentioning
confidence: 90%
“…Similar regions underwent changes in PiB SUVR, FDG SUVR, and GM volume as reported in Sabbagh et al [32] and those changes are driven by older, PiB(+) or demented participants. A number of other studies have investigated these three biomarkers in the DS population to varying extents [26, 31, 49, 5963]. As an extension of the current literature, we incorporated information from all three biomarkers into a single multi-modal voxel-wise model, and verified the regional specificity of AD-related neurodegeneration in DS.…”
Section: Discussionmentioning
confidence: 90%
“…A number of volumetric MRI studies primarily employing ROI‐based approaches (please see Annus et al, for a summary) have identified reduced overall grey matter volumes in people with Down's syndrome relative to controls (Beacher et al, ; Pearlson et al, ; White, Alkire, & Haier, ), while specific reductions in volume have also been reported in the frontal lobes, the hippocampus and the cerebellum (Aylward et al, ; Beacher et al, ; Koran et al, ; Pearlson et al, ; White et al, ). Meanwhile, increases in grey matter volume have been noted in the parahippocampal gyrus and in the parietal and occipital cortices (Beacher et al, ; White et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Brain atrophy in DS is likely to be gradual and cumulative, caused by factors such as increased amyloid deposition or secondary effects of exposure to abnormal neurodevelopment, rather than resulting from a one-off insult. While DS brains have been shown to be abnormal in size and morphology (Annus et al., 2017, Wang, 1996), brain-PAD scores did not correlate with ICV, nor does ICV correlate with brain-PAD in healthy individuals, so global size differences do not appear to be driving the results. Distinctive brain morphology in DS also did not seem to influence our findings as we observed no differences in the MAE of age prediction in the DS and control groups; age prediction accuracy was not hindered by any morphologic features of DS.…”
Section: Discussionmentioning
confidence: 99%